2013
DOI: 10.2478/jas-2013-0022
|View full text |Cite
|
Sign up to set email alerts
|

Morphmetric analysis of apis cerana populations in Huangshan, China

Abstract: A b s t r a c t Honey bees (Apis cerana Fabricius) were collected from 195 colonies at seven different localities spanning the main beekeeping areas in Huangshan. Morphometric methods were used to measure seven standard morphometric characters, and these bees were compared to samples from the Henan, Shandong, and Yunnan provinces. Principal component analysis of the total Huangshan database yielded two clusters: bees from Jinxian and Jixixian, and those from other localities. Within the latter cluster, discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…There are limited population genetic studies of Mount Huangshan A. cerana , using microsatellite analysis. A previous study by Yu et al [13], using morphometric analysis reported similar finding. Therefore, our study adds to the knowledge of the genetic changes that may be occurring in this important endemic honey bee population.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…There are limited population genetic studies of Mount Huangshan A. cerana , using microsatellite analysis. A previous study by Yu et al [13], using morphometric analysis reported similar finding. Therefore, our study adds to the knowledge of the genetic changes that may be occurring in this important endemic honey bee population.…”
Section: Discussionsupporting
confidence: 77%
“…The locations where honey bee samples were collected were mentioned in Yu et al [13]. The number and size of alleles, the value of Ho and He are listed in Additional file 1: Table S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation